Hubungan antara Religiusitas dan Machiavellian dengan Tax Evasion: Riset Berdasarkan Perspektif Gender - Dekeng Setyo Budiarto; . Yennisa; Fitri Nurmalisa (Telaah Bisnis, 2018)
Abstract Tax compliance has long been an issue for governments throughout the world and there is a large and rich research literatur in this field. This study examines the influence religiosity,and machiavellian on the tax evasion based from gender. The sample of this study are 202 accounting students from 8 private university of Special Region of Yogyakarta. The results of the study prove that religiosity has significant influence on tax evasion, while machiavellian has no significant influence on tax evasion. Moreover, there is significant different on tax evasion based from gender. The results are expected for the government to designing policies to prevent tax evasion.